Customer Interest in E-Commerce Live Streaming for Fashion Thrift Repurchases: Systematic Literature Review - Muhammad Ifantara Putra; Reny Nadlifatin (ILKOMNIKA: Journal of Computer Science and Applied Informatics, 2024)
The rapid advancement of technology has revolutionized various aspects of human life, including online shopping and information exchange via the internet. One method to do online shopping is through e-commerce. The online shopping landscape continues to evolve with the emergence of E-Commerce Live Streaming (ECLS) as a new and interactive platform for consumer engagement. This research explores the utilization of ECLS as a medium to repurchase thrift fashion, a trend driven by sustainable fashion preferences and digital retail innovation. This research analyzes the factors influencing consumer repurchase intention in the thrift fashion industry to support local clothing sellers. ECLS combines real-time video broadcasting with interactive features, creating an immersive shopping experience that goes beyond traditional online retail. Researchers selected 30 articles that were most relevant to the topic. We looked at the key drivers shaping this intersection by adopting a multidisciplinary approach, including a literature review and qualitative analysis. From the appeal of personalized advice to the excitement of witnessing the appearance of products in real-time, consumers are attracted to the unique advantages that modern technology offers in the context of sustainable fashion choices. The results show that affordable prices, good quality of goods, and the uniqueness and diversity of products are the main factors that influence repurchase interest in thrift stores. In addition, environmental awareness and sentimental value of second-hand goods also contribute significantly to repurchase intention.